2019
DOI: 10.1177/1071181319631520
|View full text |Cite
|
Sign up to set email alerts
|

Examining Training Comprehension and External Cognition in Evaluations of Uncertainty Visualizations to Support Decision Making

Abstract: Recent advances in uncertainty visualization research have focused not only on design features to support decision making, but also on challenges of evaluating the effectiveness of uncertainty visualizations, such as the degree to which individuals’ baseline task comprehension may alter their performance on experimental tasks regardless of a visualization’s effectiveness. Building on recent work, we investigated the effect of training comprehension on performance across varying representations of uncertainty a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Lang and Bailey (2015) predicted and found that stable, motivationally relevant information at the periphery of the screen (not imminent) will be remembered better than when it is in the centre (imminent). The reason for this is that the human body has evolved over time to use its environment as a store of external memory (Hollan et al , 2000; Morton, 1967; Song et al , 2019), conserving energy for memorising potentially disappearing (fleeting) information that may be needed later. Imminent, stable and relevant information is likely to be imminent, stable and relevant in the future, so it does not need effortful attention and memorising.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lang and Bailey (2015) predicted and found that stable, motivationally relevant information at the periphery of the screen (not imminent) will be remembered better than when it is in the centre (imminent). The reason for this is that the human body has evolved over time to use its environment as a store of external memory (Hollan et al , 2000; Morton, 1967; Song et al , 2019), conserving energy for memorising potentially disappearing (fleeting) information that may be needed later. Imminent, stable and relevant information is likely to be imminent, stable and relevant in the future, so it does not need effortful attention and memorising.…”
Section: Discussionmentioning
confidence: 99%
“…However, for motivationally and task-relevant objects, imminence and stability can suppress attention because of the relatively enduring presence and relevance of these objects. As previously discussed, whenever viewers need to remember information about stable objects, they can just look at them (Hollan et al, 2000;Morton, 1967;Song et al, 2019). This is useful for human survival, as it frees attention to concentrate on fleeting objects and relevant objects located peripherally (Carretié et al, 2020;Lang and Bailey, 2015).…”
Section: Influence Of Dynamic Contentmentioning
confidence: 99%
“…As one example of an additional area outside of MCQ or user surveys to measure outcomes, Cuevas et al (2004) described how "simulation vignettes" could be used to more accurately gauge the integration of knowledge in learners when compared to standard traditional assessments. This was recently tested and replicated in Song et al (2019) in studying simulations of decision making under uncertainty. But I-VR is capable of much more.…”
Section: Integrating Findingsmentioning
confidence: 97%